2014
DOI: 10.1017/s1751731113002243
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and differentiation of 12 eastern Adriatic and western Dinaric native sheep breeds using microsatellites

Abstract: Nuclear genetic diversity and differentiation of 341 sheep belonging to 12 sheep breeds from Croatia and Bosnia and Herzegovina were examined. The aim of the study was to provide the understanding of the genetic structure and variability of the analysed pramenka sheep populations, and to give indications for conservation strategies based on the population diversity and structure information. The genetic variation of the sheep populations, examined at the nuclear level using 27 microsatellite loci, revealed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
6
19
0
Order By: Relevance
“…Herdbooks for the Croatian breeds were re-established after the Croatian War of Independence, and while LIK was affected directly by the war activities, island and peninsula breeds, such as ISTc and CRE were influenced only indirectly through the decrease of the population sizes. General genetic parameters, such as low diversity in LIK, or suspicion regarding an isolate braking effect in LIK and CRE indicated by heterozygosity estimates, are in accordance with these events (Salamon et al, 2014). ISTs has been found to be less variable at the genetic level than ISTc confirming the preliminary results (Salamon et al, 2012).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Herdbooks for the Croatian breeds were re-established after the Croatian War of Independence, and while LIK was affected directly by the war activities, island and peninsula breeds, such as ISTc and CRE were influenced only indirectly through the decrease of the population sizes. General genetic parameters, such as low diversity in LIK, or suspicion regarding an isolate braking effect in LIK and CRE indicated by heterozygosity estimates, are in accordance with these events (Salamon et al, 2014). ISTs has been found to be less variable at the genetic level than ISTc confirming the preliminary results (Salamon et al, 2012).…”
Section: Resultssupporting
confidence: 63%
“…A previous study has analysed microsatellite based genetic diversity of a global Istrian population including samples from Croatia and Slovenia, as a whole, and in comparison with other autochthonous sheep breeds of Croatia (Salamon et al, 2014). In this study we present a more detailed analysis focused on the two different Istrian sheep populations to provide a scientific assessment of their current genetic structure.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the approach used, most of the studies carried out are limited to a single country (Álvarez et al, 2004;Glowatzki-Mullis et al, 2009), while historical relationships among neighbouring sheep populations suggest the need of crossborder analyses (Tapio et al, 2005(Tapio et al, , 2010Cinkulov et al, 2008;Kusza et al, 2008;Salamon et al, 2014).…”
mentioning
confidence: 99%
“…The Istrian sheep belongs to the Pramenka type, which includes several breeds and populations of sheep of the East Adriatic region. Genetic origin of these sheep was traced by Ferencakovic et al (2013), who reported a surprisingly high number of mitochondrial DNA haplotypes, despite the overall maternal homogeneity, while Salamon et al (2014), analyzing the genetic structure and variability of the Pramenka populations in order to give indications for conservation strategies, showed that the Istrian breed had maintained higher variability compared to other breeds (i.e. Kupres Pramenka), the distinctiveness being confirmed by the high number (10) of conserved private alleles (Salamon et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic origin of these sheep was traced by Ferencakovic et al (2013), who reported a surprisingly high number of mitochondrial DNA haplotypes, despite the overall maternal homogeneity, while Salamon et al (2014), analyzing the genetic structure and variability of the Pramenka populations in order to give indications for conservation strategies, showed that the Istrian breed had maintained higher variability compared to other breeds (i.e. Kupres Pramenka), the distinctiveness being confirmed by the high number (10) of conserved private alleles (Salamon et al 2014). Moreover, a previous study by Salamon et al (2012) who analyzed the genetic diversity of the two Istrian populations, Croatian and Slovenian, separately, reported a higher inbreeding coefficient for the Slovenian; then the higher frequencies of peculiar alleles like the G allele are not surprising, the Istrian sheep of the present study having Slovenian origin.…”
Section: Discussionmentioning
confidence: 99%